Pengaruh Pemanfaatan Teknologi Informasi, Pengetahuan Akuntansi, Latar Belakang Pendidikan, Umur Usaha, Dan Skala Usaha Terhadap Penggunaan Informasi Akuntansi Pada Pelaku Usaha UMKM Medan Belawan Tahun 2019-2023 - Eva MariaMagdalena Br.Manalu; Hasibuan, Rahmawaty; Rizka Hilda Siregar; Martalina Situmorang; Eka Rizki Meiwinda; Tika Handayani; Endang Verawati (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Accounting information is a system that is generally computer-based and a method for tracking accounting activities in relation to information technology resources. Based on data published by UMKM Medan Belawan. Accounting information affects the development of UMKM for micro, small and medium enterprises that use accounting information. The purpose of this study was to determine the use of information technology, accounting knowledge, educational background, business age, and business scale on the use of accounting information in micro, small and medium enterprises in Medan Belawan 2019-2023. The research method uses quantitative descriptive. Data was taken from 96 UMKM in Medan Belawan sub-district that met the sample assessment criteria. The results of this study state that the use of information technology, accounting knowledge, educational background, business age, and business scale affect the use of accounting information.